2022
DOI: 10.21273/hortsci16201-21
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Responses to Coding Combined with Horticultural Activity

Abstract: This study was conducted to determine the physiological and psychological benefits of integrating software coding and horticultural activity. Participants included 30 adults in their 20s. The subjects randomly engaged in activities—namely, connecting Arduino components, coding, planting, and a combined coding and horticultural activities. During the activity, two subjective evaluations were conducted at the end of each activity, and participants’ brain waves were measured. The spectral edge frequency 50% of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, computer activities can lead to a decrease in parasympathetic nervous system activity, which can result in tension and stress (Garde et al 2002;Hjortskov et al 2004). A study involving coding activities based on horticulture showed an increase in sustained attention as indicated by relative beta (RB) among adults (Jeong and Park 2022). Although coding and horticultural activities have, individually, demonstrated positive effects, there has been limited research on the physiological effects of combining coding and horticulture activities for students between the ages of 11 and 16 years.…”
mentioning
confidence: 99%
“…In addition, computer activities can lead to a decrease in parasympathetic nervous system activity, which can result in tension and stress (Garde et al 2002;Hjortskov et al 2004). A study involving coding activities based on horticulture showed an increase in sustained attention as indicated by relative beta (RB) among adults (Jeong and Park 2022). Although coding and horticultural activities have, individually, demonstrated positive effects, there has been limited research on the physiological effects of combining coding and horticulture activities for students between the ages of 11 and 16 years.…”
mentioning
confidence: 99%